Establishment of a reverse genetics system for an epidemic strain of porcine rotavirus JXAY01 type G5P[23]I12 - Liu, Changjin; Wei, Huangsiwu; Zhang, Xingyi; Wu, Wenjie; Shen, Zhengqiao; Luo, Feng; Deng, Shunzhou (Frontiers in Veterinary Science, 2025)
Porcine rotavirus is one of the most important pathogens causing diarrhea in newborn piglets, and the genome of this virus contains 11 double-stranded RNA segments, which are easy to be recombined among strains to produce new strains with different antigenic properties. The reverse genetics system is an informative tool for studying virus biology. Recently, adaptable plasmid-based reverse genetics systems were developed for the porcine rotavirus OSU strain; however, such systems have not been developed for epidemic porcine rotavirus genotypes in China. In this study, we successfully established a reverse genetic system based on an epidemic strain of porcine rotavirus JXAY01 isolated in recent years, which was characterized by a specific genotype constellation: G5-P[23]-I12-R1-C1-M1-A8-N1-T7-E1-H1. 11 gene segments of porcine rotavirus JXAY01 were cloned into plasmid vectors similar to the SA11 system. JXAY01 genome segment plasmids were co-transfected with 10 complementary SA11 genome plasmids, and 11 monoreassortant strains were successfully rescued. Viral replication analyses of the parental SA11 strain and the monoreassortant strains showed that the structural protein replacement monoreassortants had reduced cell proliferation compared with the parental SA11 and non-structural protein replacement strains. The recombinant rJXAY01 strain could be successfully rescued using 11 pRG-JXAY01 plasmids. Whole genome sequencing showed 12 amino acid differences between the isolate JXAY01 and the recombinant rJXAY01, but there was no significant difference in their in vitro replication ability. This study reports the reverse genetic system, which lays the foundation for further understanding of porcine rotavirus molecular biology and novel vaccine development.